Economic well-being and quality of life in the era of COVID-19 pandemic: a prelimenary review / Mahadzir Ismail ... [et al.] - Ismail, Mahadzir; Laidin, Jamilah; Mahadzir, Siti Qurratuaini (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The COVID-19 pandemic, also known as coronavirus pandemic, has implicated almost everybody and every country globally. It was caused by severe acute respiratory syndrome coronavirus 2. The coronavirus was detected in Wuhan, China in December 2019. The World Health Organization (WHO), then declared the outbreak of this virus on 30 January 2020, and as Coronavirus Pandemic on 11 March 2020. After almost a year, more than 82 million COVID-19 cases have been reported in more than 188 countries, resulting in more than 1.7 million deaths (Worldometers.info).